Can Salvia splendens ‘Red Vista’ be used in association with the mycorrhizal fungus Glomus intraradices for the assisted phytoextraction of lead from the soil in Lima, Peru? - Vicente, E. (2019)
In Peru, gasoline containing lead as a main component was used in vehicles up until 2006, when the Government banned its sale. However, since this was preceded by a century of constant use, there is a high chance that most urban soils are polluted with this heavy metal. Hyperaccumulator plants that take up heavy metals from the soil and store them in their tissues without showing any symptoms of toxicity may be the solution to this problem, as the use of these plants for phytoremediation does not require large amounts of money, can be carried out in situ, and is environmentally friendly, making it one of the best options for urban areas. However, unfortunately, there are only a few known species of hyperaccumulator plants that can be grown in urban environments. Therefore, we conducted a bioassay at the Soil Fertility Laboratory of the Agronomy Faculty at the National Agrarian University La Molina, Peru, over a period of     4 months to determine the hyperaccumulation capacity of Salvia splendens ‘Red Vista’ and to examine whether the mycorrhizal fungus Glomus intraradices can enhance the extraction of lead from the soil. After harvest, the plants were divided into three parts (roots, leaves, and inflorescences) to determine the concentrations of lead in the various tissues. We found that S. splendens ‘Red Vista’ did not accumulate high amounts of lead in its tissues even when it was associated with G. intraradices and consequently should not be considered for use in phytoextraction.